La comunicación alternativa enfocado en el aprendizaje en la Universidad Técnica De Babahoyo, Extensión Quevedo, año 2020 - Vélez Cedeño, María Jessenia (2021)
Alternative communication to social communication students allows us new avenues for personal and professional development by giving us the necessary tools to create new forms of communication and thus lead us to the acquisition of guaranteed learning in topics that are of our interests, alternative media have always existed and have encouraged the development of society. Alternative communication and learning for social change represent a change for the new global era in which we are immersed in providing ourselves with what is necessary to face the technological and increasingly developed world. This research aims to collect information that provides the necessary tools to UTB students for their training as social communicators found in the alternative media the way to social participation that benefits us all with enriching learning, therefore it is one that allows us to integrate all regardless of their conditions allowing them to actively intervene in the construction of a true Knowledge and Learning Society.